Publication of physiology theses in scientific journals: Analysis of the status from Turkey - Seringeç Akkeçeci, Nurten (Journal of Surgery and Medicine, 2019)
Aim: Theses, one of the main sources of scientific articles, are the main indicators of scientific productivity of the country. To the best our knowledge, the publication status of physiology specialty thesis have not been reported before. This study was planned in order to evaluate the publication status in scientific journals of specialty theses by physiology departments in our country. Methods: An observational study is planned. Eighty-two physiology specialty theses available in the Council of Higher Education National Thesis Center web database (https://tez.yok.gov.tr/UlusalTezMerkezi/) on February 2019, which were entered in the system via the departmental physiology units of all medical faculties in our country and published between 2004 and 2014 were included in this study. These theses were examined regarding the year they were conducted, whether the thesis is clinical or animal study, the gender of the author, the academic title of the thesis advisor, the publication status and the other characteristics of the thesis authors. Results: Forty-seven (57.3%) out of 82 physiology specialty theses that are included in our study were published in the scientific journals. Fifteen (18.3%) of these were published in a journal with Science Citation Index (SCI), 17 (20.7%) in Science Citation Index-Expanded (SCI-E), 9 (11.0%) in the other international indexes, 5 (6.1%) in Ulakbim TR index, 1 (1.2%) was published in the national peer-reviewed journals. Conclusion: It is asserted that the publication rate of the theses as articles that were written at the end of the physiology specialization training is quite high.